Faktor Perilaku dengan Kejadian Infeksi Soil Transmitted Helminths (STH) Pada Anak Sekolah Dasar - Irma; Harleli (Awatara Publisher, 2026)
Soil Transmitted Helminth (STH) infections remain a public health problem in developing countries, including Indonesia. Primary school children are the most vulnerable group to infection because they often play in the soil and have not yet fully adopted clean and healthy living behaviors. Poor home environmental conditions and unhealthy behaviors increase the risk of STH infection transmission. This study aims to analyze the relationship between environmental conditions and behaviors with the incidence of soil transmitted helminths (STH) infections in first and second-grade students at SD Negeri 94 Kendari in 2026. This study uses an analytical observational design with a cross-sectional approach. The study population comprised all first and second-grade students using total sampling techniques. Data were collected through interviews using questionnaires, observations of respondents' home environmental conditions, and stool examinations in the laboratory. Data analysis was performed using the Chi-square test. The research results indicate that there is a significant relationship between the habit of washing hands with soap (p = 0.008) and the habit of trimming nails (p = 0.018) with the occurrence of STH infection. Meanwhile, the use of footwear (p = 0.511) is not significantly related to the occurrence of STH infection.